Plan tecnológico para migración a cloud computing de las infraestructuras y servicios de clientes pymes en CNT – EP - Zúñiga Avellán, Walter Paúl (2019)
The objective of this titling work was to develop an operational plan for migration to Cloud Computing of the infrastructures and services of PYMEs clients in CNT-EP (National Telecommunications Corporation - Public Company) of Manabí, which would allow improving the technological management of the companies. The PPDIOO methodology (Prepare, Plan, Design, Implement, Operate and Optimize) was used for its execution, using only the first three phases. In the first phase of preparation, it was used two structured questionnaires with multiple-choice and closed questions, which allowed determining the needs that consumers companies have in the use of IT and the analysis of the current systems for optimization to Cloud Computing. Then the planning continued, where the steps for the migration of data to the cloud were identified. In the third and last phase to be used, the design of a migration model was formulated, resulting in the realization of a plan that proposes guidelines to apply this migration to the different models of Cloud services most used such as IAAS and SAAS, taking into consideration that these solutions will contribute to the improvement of productivity and management of resources (people, infrastructure, information and processes) of organizations.